Enhancing Community School Teachers’ Training: A Strategic Approach to Human Resource Development - Mainali, Bhawani Prasad (Teacher Half-Yearly Journal, 2025)
The study aims at examining the effects of strategic approaches to human resource development to enhance the quality of teacher training in community schools. Training should be linked with strategic human resource development to achieve the objectives of organizations. This study employs qualitative assumptions and case study research approach. Two research questions focusing on improving the training of community school teachers' and their relationship to the strategic framework for human resource development. This study incorporates six teachers from two community schools within Kathmandu Metropolitan City. The study revealed that strategic human resource development, through targeted professional development programs and continuous performance evaluations, significantly improved the quality of teacher training in community schools. Furthermore, mentorship programs, ongoing professional development workshops and feedback are identified as the most effective techniques in enhancing teacher training. Proper implementation of strategic human resource development methods can assure teachers' ongoing professional development, which will improve instruction and achievement among students.